An architecture for aggregating information from distributed data nodes for industrial internet of things. (February 2017) - Zhu, Tao; Dhelim, Sahraoui; Zhou, Zhihao; Yang, Shunkun; Ning, Huansheng
Highlights: A service-oriented architecture for aggregating ontological information from distributed data nodes for internet of things. Semantic technologies serve as the solution to the heterogeneity of applications. Product tracing is taken as example to demonstrate the work flow of the proposed architecture. Graphical abstract: Abstract: The current Internet of Things (IoT) has made it very convenient to obtain information about a product from a single data node. However, in many industrial applications, information about a single product can be distributed in multiple different data nodes, and aggregating the information from these nodes has become a common task. In this paper, we provide a distributed service-oriented architecture for this task. In this architecture, each manufacturer provides service for their own products, and data nodes keep the information collected by themselves. Semantic technologies are adopted to handle problems of heterogeneity and serve as the foundation to support different applications. Finally, as an example, we illustrate the use of this architecture to solve the problem of product tracing.